2009
DOI: 10.1186/cc7786
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and haemodynamic changes during decremental open lung positive end-expiratory pressure titration in patients with acute respiratory distress syndrome

Abstract: IntroductionTo investigate haemodynamic and respiratory changes during lung recruitment and decremental positive end-expiratory pressure (PEEP) titration for open lung ventilation in patients with acute respiratory distress syndrome (ARDS) a prospective, clinical trial was performed involving 12 adult patients with ARDS treated in the surgical intensive care unit in a university hospital.MethodsA software programme (Open Lung Tool™) incorporated into a standard ventilator controlled the recruitment (pressure-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 44 publications
0
67
0
16
Order By: Relevance
“…The PiCCO apparatus was set up for the intermittent transpulmonary thermodilution technique, which initially injected 20 mL of iced saline into the central venous catheter before the first set of measurements, and then repeated the injection three times to obtain the mean parameters. 11 Hemodynamic data were collected before and 1 h after the surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PiCCO apparatus was set up for the intermittent transpulmonary thermodilution technique, which initially injected 20 mL of iced saline into the central venous catheter before the first set of measurements, and then repeated the injection three times to obtain the mean parameters. 11 Hemodynamic data were collected before and 1 h after the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…11 The PiCCO was used to monitor the hemodynamic parameters and intravascular volume in all patients. Hemodynamic data were the primary outcome of the present study.…”
Section: Methodsmentioning
confidence: 99%
“…This is not a new approach to determining an optimal level of PEEP. [7][8][9][10][11][12] However, a quick look at the available evidence may leave clinicians questioning the usefulness of this method. In the provided Table of decremental PEEP studies there are noticeable differences in titration methods, monitored values, methods for prior recruitment, as well as what the "optimal" level of PEEP should be post procedure.…”
Section: Decremental Peep Titrationmentioning
confidence: 99%
“…PEEP provides higher alveolar stability after the recruitment. The ideal PEEP can be determined by the best gas exchange point, in other words, 2 cmH2O above the lower inflection point of pressure-volume curve of the respiratory system, observing the hemodynamic stability [10,20,26 Benefits Studies have shown that alveolar recruitment strategies can improve respiratory function in the postoperative period of cardiac surgery by reducing atelectasis and intrapulmonary shunt, improving ventilation-perfusion ratio and, consequently, arterial oxygenation [11,13,16].…”
Section: Adverse Effects and Contraindicationsmentioning
confidence: 99%